The emperor of Nihon-Ja - Flanagan, John (John Anthony) (New York : Philomel Books, 2011)
In a faraway land, a young warrior must protect an emperor from an uprising and train an inexperienced army, with assistance from his Ranger friends.
Booklist, March 2011.
Booklist.
6.4
5-8
Keywords: Kings and rulers -- Juvenile fiction; Kings, queens, rulers, etc. -- Fiction; Fantasy; Kings and rulers -- Fiction; Fantasy fiction; Fantasy; Kings, queens, rulers, etc. -- Fiction; Fantasy fiction